2016
DOI: 10.1038/srep20960
|View full text |Cite
|
Sign up to set email alerts
|

Theta synchronization between medial prefrontal cortex and cerebellum is associated with adaptive performance of associative learning behavior

Abstract: Associative learning is thought to require coordinated activities among distributed brain regions. For example, to direct behavior appropriately, the medial prefrontal cortex (mPFC) must encode and maintain sensory information and then interact with the cerebellum during trace eyeblink conditioning (TEBC), a commonly-used associative learning model. However, the mechanisms by which these two distant areas interact remain elusive. By simultaneously recording local field potential (LFP) signals from the mPFC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…Neuronal coherence has been described across the cerebro-cerebellar system at a variety of low frequencies [9,6671] and oscillations within the theta range are thought to support inter-region communication across a wide variety of brain regions [72]. Our finding that cerebello-hippocampal coherence is limited to the 6-12 Hz bandwidth is in keeping with previous studies on cerebro-cerebellar communication in which neuronal synchronization has been observed between the cerebellum and prefrontal cortex [9,67], primary motor cortex [66,70], supplementary motor area [66] and sensory cortex [66]. Furthermore, local field potentials recorded in the hippocampus and cerebellar cortex are synchronized within the theta bandwidth during trace eye-blink conditioning in rabbits [73].…”
Section: Discussionsupporting
confidence: 90%
“…Neuronal coherence has been described across the cerebro-cerebellar system at a variety of low frequencies [9,6671] and oscillations within the theta range are thought to support inter-region communication across a wide variety of brain regions [72]. Our finding that cerebello-hippocampal coherence is limited to the 6-12 Hz bandwidth is in keeping with previous studies on cerebro-cerebellar communication in which neuronal synchronization has been observed between the cerebellum and prefrontal cortex [9,67], primary motor cortex [66,70], supplementary motor area [66] and sensory cortex [66]. Furthermore, local field potentials recorded in the hippocampus and cerebellar cortex are synchronized within the theta bandwidth during trace eye-blink conditioning in rabbits [73].…”
Section: Discussionsupporting
confidence: 90%
“…Neuronal coherence has been described across the cerebro-cerebellar system at a variety of low frequencies (O'Connor et al, 2002; Courtemanche and Lamarre, 2005; Soteropoulos and Baker, 2006; Rowland et al, 2010; Frederick et al, 2014; Watson et al, 2014; Chen et al, 2016) and oscillations within the theta range are thought to support inter-region communication across a wide variety of brain regions (Colgin, 2013). Our finding that cerebello-hippocampal coherence is limited to the 6–12 Hz bandwidth is in keeping with previous studies on cerebro-cerebellar communication in which neuronal synchronization has been observed between the cerebellum and prefrontal cortex (Watson et al, 2014; Chen et al, 2016), primary motor cortex (Soteropoulos and Baker, 2006; Rowland et al, 2010), supplementary motor area (Rowland et al, 2010) and sensory cortex (Rowland et al, 2010). Furthermore, LFPs recorded in the hippocampus and cerebellar cortex are synchronized within the theta bandwidth during trace eye-blink conditioning in rabbits (Hoffmann and Berry, 2009; Wikgren et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellum is thought to play an important role in cognitive function through its interactions with the prefrontal cortex (Hoppenbrouwers et al, 2008; Strick et al, 2009; Bostan et al, 2013). Both slow and fast oscillatory rhythms are thought to coordinate interactions between the cerebellum and cortical sites (O’Connor et al, 2002; Courtemanche and Lamarre, 2005; Ros et al, 2009; Courtemanche et al, 2013; Popa et al, 2013; Chen et al, 2016), and rhythmic cerebellar stimulation has been used as a therapeutic intervention in some disorders (Schutter et al, 2003; Schutter and van Honk, 2006, 2009; Demirtas-Tatlidede et al, 2010). The present study has examined the effects of cerebellar vermal stimulation at various rhythms on the entrainment of cerebellar and cortical LFPs under urethane anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Coherent activity in the alpha and beta frequency ranges occurs in the cerebellum and sensorimotor cortex during actions requiring somatosensory monitoring (O’Connor et al, 2002; Courtemanche and Lamarre, 2005). Functionally as well, synchronization of LFPs between the medial prefrontal cortex and the cerebellum at 5–12 Hz has been linked with adaptive performance in eyeblink conditioning during the early stages of learning (Chen et al, 2016). Multiple brain regions, including the amygdala, hippocampus, medial prefrontal cortex, and cerebellum must coordinate to acquire a variety of learned responses, such as the conditioned eyelid response in the eyeblink conditioning paradigm (Lee and Kim, 2004).…”
Section: Discussionmentioning
confidence: 99%